Performance Evaluation of Turtle Excluder Device off Dhamra in Bay of Bengal - Prakash, R. Raghu; Boopendranath, M. R.; Vinod, M. (Fishery Technology, 2025)
Turtles are endangered and protected species underthe Indian Wildlife Protection Act 1972. A numberof non-target resources, such as sea turtles, arecaught during trawling. This study reports the fieldtrials conducted using TED-installed fish trawls inOdisha waters to evaluate the efficacy of TED. Theincidence of sea turtles was one for every 15 haulsand the turtle excluder device (CIFT-TED) showed100% exclusion for the sea turtle entering the trawlsystem. The exclusion rates were 2.5% for the totalcatch and 2.7% for the shrimp. Twenty eight speciesof finfish were encountered during the trials ofwhich 17 were represented in the excluded portionof the catch.